Neurohumoral relationship in patients with rheumatic diseases - I. V. Dryazenkova; A. V. Arshinov (Научно-практическая ревматология, 2004)
Objective. To assess neurohumoral relationship state in pts with systemic vasculitis (SV) and systemic connective tissue diseases. Material and Methods. 54 pts with rheumatic diseases (RS) were included: 18 with systemic lupus erythematosus (SLE), 16 with systemic sclerosis, 20 with systemic vasculitis (SV). Mean age was 49,3 5,4 years. Disease duration varied from 5 to 10 years. Control group consisted of 20 healthy persons. 24- hours ECG monitoring, heart rate variability (HRV) spectral analysis, functional (clinoorthostatic sign) and exercise ECG testing (isometric exercise, dynamic load, veloergometry) were performed. Plasma histamine level, histaminase activity, plasma serotonin, tryptophan-5-hydrolase, oxytriptophandecar- boxylase, MAO levels were examined to assess vasoactive amine system state. Vasoactive amine system slate was assessed on histamine/serotonin ratio. Histamine/histaminase, serotonin/MAO, histaminase/MAO ratios were used to judge inhibitory activity. Results. Compared with control pts with RS showed marked and significant decrease of ergotropic mediators (noradrenaline, adrenaline) and their metabolites concentration which correlated with HRV. Increase of histaminase that processes appropriate biogenic amine excess quantity was found in all forms of RS. More intensive than in healthy persons monoamine metabolism accompanied by their degradation acceleration resulted in enhanced MAO activity (significant in polyarteritis). LF/HF index reflecting summated activity of autonomic influences on heart rate showed significant prevalence of sympathetic effect in SV (3,46 0,31, p<0,05), CRV analysis showed adequate autonomic supply only in 11,7% of pts with RS. Conclusion. Exercise testing in dynamic analysis of quantitative HRV indices should be performed to determine autonomic reactivity ю assess homeostatic possibilities and adaptation reserve in pts with RS.